Perception of mental illness in ancient Greek and contemporary (2018)
Mental illness is one of the most dreaded illnesses in human societies. Recent studies have investigated the phenomenon as neurosis with psychotic manifestations in individuals across societies. However, there are diverse opinions on the cause(s) of mental illness. Therefore, interrogating the subject from the worldviews of two traditional societies— Ancient Greece and Yoruba - the study classifies the causes of mental illness into three: natural, physical and supernatural. It further investigates attitudinal correlation between societies in the classical era and modern times in the perception of mental disorders. The aims to detarmine if prejudices or biases are proximal or distal in both societies and to highlight the social implications for interpersonal relationships, especially as bases for the acceptance and social instability of those who experience mental illness. The study, which is basically descriptive, adopts philosophical and cultural analytical methods to foreground textual explication, using the works of Plato, Hippocrates, Oluwole and Jegede. The paper shows that both in Ancient Greece and Yoruba societies, mental illness is attributed to retribution from the gods and accounts for the preponderance of Greek mythologies and tragedies, contextualising madness as inflicted by wrathful or envious gods or goddesses. It concludes that the stigmatisation of affected persons often emasculates them as they are deprived of proper healthcare during the period of illness, and denied social protection and recognition if they are fortunate enough to receive treatment. Invariably, the society is impoverished through this latent brain drain.